(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
The cocoa industry in Ghana is plagued with a number of challenges. Among such challenges is the issue of insecurity. This notwithstanding, there are limited scholarly findings on the nature and the underlying factors associated with these insecurity issues. This paper examined the cocoa industry in the Sefwi Akontombra District in the Western Region of Ghana and presents an analysis of the processes and procedures for cocoa purchasing in the district; the security arrangements and mechanisms put in place during cocoa purchasing peak periods; the nature of access roads in cocoa growing areas in the district; and the influence of access roads on the insecurity of cocoa purchasing in the district. The study adopted a qualitative research approach and using a cross sectional study design, the case of OLAM Ghana Limited, a private licensed cocoa buying company operating in Sefwi Akontombra was examined. Primary data were gathered from purchasing clerks, drivers, warehouse keepers and officials of the company. Data from the District Command of the Ghana Police Service and the Department of Feeder Roads district office were solicited using interview guides. Non-participant observation and taking of photography were also employed as data capturing mechanism during the study. The study espoused content analysis in analysing the contents of the interviews and observational field notes in order to identify the main themes that emerge from the responses given by the respondents or the observation notes made. Inferences and implications were drawn then drawn from the analysis. The study found out that there was no security measure by OLAM Ghana Limited to ensure the safety of funds meant for cocoa buying, the storage and the transportation of cocoa beans in the study district. There was also no security arrangement during peak cocoa purchasing periods in the study district by key stakeholders within the cocoa sector in the district. Moreover, access road was further found out to be a major factor that accounts for some of the insecurity issues associated with cocoa purchasing activities in the Sefwi Akontombra District. The study thus recommends the development and adoption of security arrangements and mechanism by all stakeholders within the cocoa industry in the study district and the making of security issues a top priority by OLAM Ghana Limited.